2018
DOI: 10.1016/j.bbabio.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma infection and hypoxia initiate succinate accumulation and release in the VM-M3 cancer cells

Abstract: Succinate is known to act as an inflammatory signal in classically activated macrophages through stabilization of HIF-1α leading to IL-1β production. Relevant to this, hypoxia is known to drive succinate accumulation and release into the extracellular milieu. The metabolic alterations associated with succinate release during inflammation and under hypoxia are poorly understood. Data are presented showing that Mycoplasma arginini infection of VM-M3 cancer cells enhances the Warburg effect associated with succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Complete inhibition of OxPhos and glycolysis by oligomycin and 2-DG in CSCs and non-CSCs caused more substrate-level phosphorylation in uPAR+ CSCs. Under respiratory distress conditions, substrate-level phosphorylation provides the necessary GTP/ATP to CSCs and this is more efficient under hypoxic conditions ( 228 , 229 ). In vivo and ex vivo studies in OxPhos defective mtDNA mutated cybrid A6MT cells and wild type cells that have no mtDNA mutations, showed that Glutamine accelerates the proliferation of A6MT cell and its uptake was higher in mtDNA mutated cells than in wild type cells.…”
Section: Metabolism Of Glutamine In Cscsmentioning
confidence: 99%
“…Complete inhibition of OxPhos and glycolysis by oligomycin and 2-DG in CSCs and non-CSCs caused more substrate-level phosphorylation in uPAR+ CSCs. Under respiratory distress conditions, substrate-level phosphorylation provides the necessary GTP/ATP to CSCs and this is more efficient under hypoxic conditions ( 228 , 229 ). In vivo and ex vivo studies in OxPhos defective mtDNA mutated cybrid A6MT cells and wild type cells that have no mtDNA mutations, showed that Glutamine accelerates the proliferation of A6MT cell and its uptake was higher in mtDNA mutated cells than in wild type cells.…”
Section: Metabolism Of Glutamine In Cscsmentioning
confidence: 99%
“…Dysbiosis is observed in lungs of patients of COPD, in that the composition of lungs microbiota is less diverse than the one observed in healthy persons, and has a tendency to be restricted to phyla comprising potentially pathogenic microorganism, including M. pneumoniae [24,27,28], also associated with acute exacerbation [29,30]. Some of the mechanisms by which M. pneumoniae could enhance the negative effects of tobacco products in COPD patients is by increasing oxidative stress [31], inflammation status and hypoxia-related factors, such as HIF-1α [32]. Quitting smoking in combination with anti-muscarinic bronchodilators resulted in an improvement of lung function and respiratory symptoms in mild COPD patients and it could be interesting to determine whether this would also result in a reduction in dysbiosis and the presence of M. pneumoniae [24].…”
Section: Mycoplasma and Copdmentioning
confidence: 99%
“…Succinate plays important role in the inflammation process (Mills & O'Neill, ; Tannahill et al, ). Calcium‐dependent NO and PGE2 production were observed following stimulation of SUCNR1 with succinate (Flores et al, ; Tannahill et al, ). Succinate acts in synergy with the TLR3 ligand poly (I:C) and the TLR7 ligand imiquimod, thereby increasing the TNF‐ α production and expression (Tannahill et al, ).…”
Section: Discussionmentioning
confidence: 99%